A toxin-based approach to neuropeptide and peptide hormone discovery - Koch, Thomas Lund; Torres, Joshua P.; Baskin, Robert P.; Salcedo, Paula Flórez; Chase, Kevin; Olivera, Baldomero M.; Safavi-Hemami, Helena (Frontiers in Molecular Neuroscience, 2023)
Peptide hormones and neuropeptides form a diverse class of bioactive secreted molecules that control essential processes in animals. Despite breakthroughs in peptide discovery, many signaling peptides remain undiscovered. Recently, we demonstrated the use of somatostatin-mimicking toxins from cone snails to identify the invertebrate ortholog of somatostatin. Here, we show that this toxin-based approach can be systematically applied to discover other unknown secretory peptides that are likely to have signaling function. Using large sequencing datasets, we searched for homologies between cone snail toxins and secreted proteins from the snails’ prey. We identified and confirmed expression of five toxin families that share strong similarities with unknown secretory peptides from mollusks and annelids and in one case also from ecdysozoans. Based on several lines of evidence we propose that these peptides likely act as signaling peptides that serve important physiological functions. Indeed, we confirmed that one of the identified peptides belongs to the family of crustacean hyperglycemic hormone, a peptide not previously observed in Spiralia. We propose that this discovery pipeline can be broadly applied to other systems in which one organism has evolved molecules to manipulate the physiology of another.